What’s wrong with Pittsburgh? Delegated investors and liquidity concentration - Ghent, Andra C. (Journal of Financial Economics, 2021)
What makes an asset institutional quality? This paper proposes that one reason is the existing concentration of delegated investors in a market through a liquidity channel. Consistent with this intuition, it documents differences in investor composition across US cities and shows that delegated investors concentrate their investments in cities with higher turnover. It then estimates a search model showing how heterogeneity in liquidity preferences makes some markets more liquid, even when assets have identical cash flows. The paper provides evidence for clientele equilibria arising in frictional asset markets and suggests that a liquidity channel may explain divergent paths in city development.